The Development of a Model for Complaint Delivery on Aviation Industry in Indonesia Based on SMS Gateway to Promote Flight Safety - Riani Nurdin; Eko Poerwanto; Haruno Sajati (Institut Teknologi Bandung, 2019)
The variety of complaints appearing on Aviation Industry in Indonesia actually indicates the existence of problems on aviation system in Indonesia. The number of complaints may serve as an early detection in a system before the occurrence of an accident in a flight. Increasing numbers of flight service users in Indonesia had not been supported with an adequate complaint delivery, whether it is for internal complaints or external ones. One of available solutions is to detect whether all system components on Aviation Industry in Indonesia is good or not. In an effort to enhance system performance, a model for integrated complaint delivery is developed on Aviation Industry based on SMS Gateway in Indonesia. The model is expected to become a data bank on Aviation Industry to ease controlling, evaluating and improving condition performance on flight systems. This research used comparative and descriptive methods. It also results in applied product hence it is expected that the output can be used to complement the current product/program operated by Directorate General of Civil Aviation (DGCA). The development of a model for complaint delivery is conducted to make cellular phone numbers inputs for all stakeholders on aviation industry. This strategy activates all stakeholders to provide information regarding the current conditions for all subsystems in flight system in Indonesia